Respon Ayam Ras Petelur Terhadap Penambahan Asam Humat Pada Ransum Yang Mengandung Bungkil Inti Sawit Dan Bungkil Inti Sawit Fermentasi - Mirnawati Mirnawati (Jurnal Embrio, 2011)
The experiment was conducted to know the layer response of humic acid addition in ration which used the palm kernel cake (PKC) and the palm kernel cake fermented (PKCF). This experiment used complete randomize design (CRD) with 4 treatments and 6 replications. The treatments were arranged as follows: 1) 0% basic ration (0% PKC/PKCF), 2) 15% PKCF, 3) 15% PKC + 0,2% humic acid, 4) 15% PKCF +0,2% humic acid. The ration were formulated iso protein 16% and iso caloric 2700 kkal /kg ration. Variabels of this study were egg production, egg weight, and thick cell . The result of this study showed that egg production, egg weight, and thick cell were highly significant (P>0,05) by any treatment. The conclusion that palm kernel cake fermented (PKCF) by Aspergillus niger were used 15% in layer ration, give the best result, with 67,79% egg production, 66,72 gr/each egg weight and 0,12mm thick cell .